Allograft biopsy findings in patients with small bowel transplantation. Issue 11 (26th September 2016) - Koo, Jamie; Dawson, David W.; Dry, Sarah; French, Samuel W.; Naini, Bita V.; Wang, Hanlin L.
Abstract: In this study, we sought to determine the incidence of post‐transplant complications including acute cellular rejection (ACR), infection, and post‐transplant lymphoproliferative disease (PTLD) in mucosal allograft biopsies in patients with small bowel transplant at our institution. We retrospectively reviewed pathology reports from 5675 small bowel allograft biopsies from 99 patients and analyzed the following: indications for biopsy, frequency and grade of ACR, the presence of infectious agents, results of workup for potential PTLD, results of C4d immunohistochemistry (IHC), features of chronic mucosal injury, and findings in concurrent native bowel biopsies. Findings from 42 allograft resection specimens were also correlated with prior biopsy findings. Indeterminate, mild, moderate, and severe ACR were seen in 276 (4.9%), 409 (7.2%), 100 (1.8%), and 207 (3.6%) of biopsies, respectively. Although ACR may show histologic overlap with mycophenolate mofetil toxicity, we found the analysis of concurrent native bowel biopsies to be helpful in this distinction. Adenovirus was the most common infectious agent seen (11%), and we routinely performed adenovirus IHC on biopsies. Eighteen patients (18%) developed PTLD, 83% of which were EBV associated, but only 28% of PTLD cases were diagnosed on mucosal allograft biopsies. C4d IHC did not correlate with the presence of donor‐specific antibodies in limited cases.